2013
DOI: 10.1155/2013/459390
|View full text |Cite
|
Sign up to set email alerts
|

In VitroScreening for Antihepatic Steatosis Active Components within Coptidis Rhizoma Alkaloids Extract Using Liver Cell Extraction with HPLC Analysis and a Free Fatty Acid-Induced Hepatic Steatosis HepG2 Cell Assay

Abstract: A high-throughput method was developed and applied to screen for the active antihepatic steatosis components within Coptidis Rhizoma Alkaloids Extract (CAE). This method was a combination of two previously described assays: HepG2 cell extraction with HPLC analysis and a free fatty acid-induced (FFA) hepatic steatosis HepG2 cell assay. Two alkaloids within CAE, berberine and coptisine, were identified by HepG2 cell extraction with HPLC analysis as high affinity components for HepG2. These alkaloids were also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…The tested extract at the concentration of 12.5 to 100.0 µg/mL had a triglycerides reducing effect in a dose-dependent manner. MGN and other alkaloids from the extract like epiberberine, palmatine, or columbamine reduced triglyceride level in a statistically significant way only at the highest concentration applied (5.0 µg/mL) [71].…”
Section: The Effect On Carbohydrate-lipid Metabolismmentioning
confidence: 90%
See 1 more Smart Citation
“…The tested extract at the concentration of 12.5 to 100.0 µg/mL had a triglycerides reducing effect in a dose-dependent manner. MGN and other alkaloids from the extract like epiberberine, palmatine, or columbamine reduced triglyceride level in a statistically significant way only at the highest concentration applied (5.0 µg/mL) [71].…”
Section: The Effect On Carbohydrate-lipid Metabolismmentioning
confidence: 90%
“…In vitro screening of alkaloid-rich liver cell extract obtained after the administration of Coptidis rhizoma and a free fatty acid-induced test for hepatic steatosis HepG2 cell assay was performed by Fan and colleagues [71]. Hepatic steatosis characterized by overmuch fat accumulation in hepatocytes is a serious clinical problem.…”
Section: The Effect On Carbohydrate-lipid Metabolismmentioning
confidence: 99%
“…HepG2 cells were obtained from the National Centre for Cell Science, Pune, India (local repository for the American Type Cell Culture (ATCC)), proliferated within two passage numbers, and stored in liquid nitrogen at passage number 17. Cells were cultured in high glucose (4.5 gm/L) DMEM cell culture media (Gibco, Evansville, IN, USA) supplemented with 10% FBS (HiMedia, Mumbai, India) and 100 U/mL penicillin/streptomycin (Thermo Fisher Scientific, Waltham, MA, USA) and maintained at 37 °C and 5% CO 2 [ 63 ]. Cells were passaged at 70% confluence and used for assays based on the number of cells required in each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…During the past decades, many pharmacokinetic studies have been focused on the intracorporal process of formulas like SHXXT and BanXia Xiexin decoctions, the main constituents of which were all verified to include coptisine (Chemical structure showed in Figure ). In rat model administrated with SHXXT, coptisine was not metabolized in blood and could reach hepatic and liver cells as prototype form . To evaluate further coptisine metabolism in liver, a study conducted in zebrafish model demonstrated that coptisine has 4 metabolites and the main metabolic ways include demethylation, hydroxylation, sulphation and glucuronidation .…”
Section: Intracorporal Processmentioning
confidence: 99%
“…In rat model administrated with SHXXT, coptisine was not metabolized in blood and could reach hepatic and liver cells as prototype form. 17 To evaluate further coptisine metabolism in liver, a study conducted in zebrafish model demonstrated that coptisine has 4 metabolites and the main metabolic ways include demethylation, hydroxylation, sulphation and glucuronidation. 18 Moreover, coptisine was revealed to be the substrate of P-gp, 19 which to some extent, contributes to the low distribution of coptisine in multiple tissues.…”
Section: Intr Acorp or Al Pro Ce Ssmentioning
confidence: 99%